2016
DOI: 10.15171/jrip.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit/hyperactivity disorder in children with overactive bladder; a case-control study

Abstract: Introduction: Attention-deficit/hyperactivity disorder (ADHD) is the most common childhood psychiatric disorder. This disorder is more prevalent in some chronic diseases. Objectives: To investigate ADHD in children with overactive bladder. Patients and Methods: A number of 92 children with overactive bladder and 92 healthy children without overactive bladder (age range of both groups 5 to 12 years old) were included in this study as case and control groups, respectively. Participants were selected from child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…The fact that ADHD is more common in children with overactive bladder than in healthy children is already established. 26 The incidence of pain was similar in those with an ADHD diagnosis compared to those without an ADHD diagnosis. Our theory that children with ADHD have an increased sensitivity to pain stimuli was not borne out in our study, nor did treatment with central stimulants result in a reduced frequency of reported pain in the patients’ medical records.…”
Section: Discussionmentioning
confidence: 87%
“…The fact that ADHD is more common in children with overactive bladder than in healthy children is already established. 26 The incidence of pain was similar in those with an ADHD diagnosis compared to those without an ADHD diagnosis. Our theory that children with ADHD have an increased sensitivity to pain stimuli was not borne out in our study, nor did treatment with central stimulants result in a reduced frequency of reported pain in the patients’ medical records.…”
Section: Discussionmentioning
confidence: 87%
“…P. Yousefichaijan и соавт. [38] обследовали 92 ребенка с гиперактивным мочевым пузырем и сравнили данные с контрольной группой. Результаты исследования показали, что у детей с гиперактивным мочевым пузырем (35,9%) СДВГ встречается достоверно чаще, чем у детей контрольной группы (19,6%).…”
Section: таблица частота энуреза у детей страдающих нарушениями дыхunclassified
“…However, ADHD is often comorbid with other psychiatric disorders [4, 5] and medical conditions. Comorbidity with lower urinary tract symptoms [6, 7] and overactive bladder syndrome [8, 9] has been reported.…”
Section: Introductionmentioning
confidence: 99%